2023
DOI: 10.3390/rs15204898
|View full text |Cite
|
Sign up to set email alerts
|

Mask R-CNN–Based Landslide Hazard Identification for 22.6 Extreme Rainfall Induced Landslides in the Beijiang River Basin, China

Zhibo Wu,
Hao Li,
Shaoxiong Yuan
et al.

Abstract: Landslides triggered by extreme precipitation events pose a significant threat to human life and property in mountainous regions. Therefore, accurate identification of landslide locations is crucial for effective prevention and mitigation strategies. During the prolonged heavy rainfall events in Guangdong Province between 21 May and 21 June 2022, shallow and clustered landslides occurred in the mountainous regions of the Beijiang River Basin. This research used high-resolution satellite imagery and integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Yang et al [87] addressed the problem of erroneous extraction due to confusing features, added landslide triggering factors as auxiliary information in the input image data to achieve the purpose of background enhancement, and verified the feasibility of the method using the Mask R-CNN model: the accuracy was 88.68%. Wu et al [88] combined the Mask R-CNN model with the deciphered markers of landslides in remote sensing imagery for landslide identification, and the results showed that the overall accuracy of the method for landslide identification was close to 90%.…”
Section: Mask R-cnnmentioning
confidence: 99%
“…Yang et al [87] addressed the problem of erroneous extraction due to confusing features, added landslide triggering factors as auxiliary information in the input image data to achieve the purpose of background enhancement, and verified the feasibility of the method using the Mask R-CNN model: the accuracy was 88.68%. Wu et al [88] combined the Mask R-CNN model with the deciphered markers of landslides in remote sensing imagery for landslide identification, and the results showed that the overall accuracy of the method for landslide identification was close to 90%.…”
Section: Mask R-cnnmentioning
confidence: 99%
“…Yu et al [40] developed a hierarchical-attention multi-scale deconvolution network and yielded 21% higher F1 scores for landslide identification compared with six networks (Unet, SegNet, DeepLabv3, PSPNet, BiSeNet). Wu et al [43] employed the mask R-CNN model and combined spectral, textural, morphological, and physical characteristics to extract rainfall-induced landslides in Beijiang River Basin with a precision rate of 81.91%, a recall rate of 84.07%, and an overall accuracy of 87.28%. Fu et al [44] proposed the YOLOv3 network and InSAR phase-gradient stacking maps to extract 3366 slow-moving landslides in southwestern China.…”
Section: Introductionmentioning
confidence: 99%